Endovascular Repair for Ruptured Axillary Artery Aneurysm Proximal to Hemodialysis Access. (July 2019) - Takigawa, Tomoya; Tokunaga, Shigehiko; Baba, Hironori; Hisahara, Manabu; Ochiai, Yoshie; Ando, Yusuke; Miyagi, Chihiro
Axillary artery aneurysms are uncommon and potentially high-risk lesions threatening the upper extremities. In hemodialysis patients, arteriovenous fistulae creation rarely triggers aneurysmal degeneration and arterial aneurysms in inflow arteries. These aneurysms are usually treated by surgical repair. However, this may lead to complications because of the anatomical complexity surrounding aneurysms of axillary arteries. We report a patient undergoing hemodialysis who had a ruptured ipsilateral axillary artery aneurysm proximal to vascular access. We successfully treated it by endovascular repair with the GORE Excluder AAA contralateral leg endoprosthesis, approaching from the left brachial artery proximal to the shunt. No complications occurred during 15 months after the endovascular repair.